Salmon‐derived nutrient and organic matter fluxes from a coastal catchment in southeast Alaska. (21st March 2019) - Hood, Eran; Fellman, Jason B.; Edwards, Rick T.; D'Amore, David V.; Scott, Durelle
Abstract: Salmon are important vectors for biogeochemical transport across ecosystem boundaries. Here we quantified salmon contributions to annual catchment fluxes of nutrients (N and P) and organic matter (C, N, and P) from a forested catchment in coastal southeast Alaska. Concentrations of ammonium and soluble reactive phosphorus increased by several orders of magnitude during spawning and were significantly correlated with spawning salmon densities. Nitrate concentrations increased modestly during spawning and were not significantly correlated with salmon densities. Salmon had a modest legacy effect on inorganic N and P as evidenced by elevated streamwater concentrations past the end of the spawning period. Dissolved organic carbon concentrations did not respond to the presence of salmon; however, concentrations of dissolved organic nitrogen and phosphorus showed a significant positive relationship to salmon densities. Changes in spectroscopic properties of the bulk streamwater dissolved organic matter pool indicated that streamwater dissolved organic matter became less aromatic and biolabile during spawning. On an annual basis, salmon were the dominant source of streamwater fluxes of inorganic nutrients, accounting for 92%, 65%, and 74% of annual streamwater fluxes of ammonium, nitrate, and soluble reactive phosphorus, respectively. In contrast, fluxes of organic matter were dominated by catchment sources with salmon accounting for <1% of the annual catchment flux of dissolved organic carbon and 12% and 15% of the annual fluxes of dissolved organic nitrogen and phosphorous respectively. These findings indicate that, in small coastal catchments, salmon can be a quantitatively important source of dissolved streamwater nutrients with implications for productivity in downstream estuarine ecosystems.